KEDUDUKAN ANAK DI LUAR PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 DALAM PERSPEKTIF HUKUM ISLAM - Istiqomah; Nelli, Jumni (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This article examines the legal status of children born outside of marriage as a significant issue within the Indonesian legal system, particularly after the Constitutional Court Decision Number 46/PUU-VIII/2010. Prior to this decision, a child born outside of marriage was legally recognized as having a civil relationship only with the mother and her family, as stipulated in Article 43 paragraph (1) of the Marriage Law. The Constitutional Court’s ruling introduced a fundamental shift by allowing the possibility of establishing a civil relationship with the biological father, provided that scientific evidence—such as DNA testing—can prove a biological link. This development creates new dynamics in the protection of children's rights, especially regarding legal status, maintenance, and inheritance rights. This study aims to comprehensively analyze the position of children born outside of marriage after the Constitutional Court’s decision, viewed from both national law and Islamic law perspectives.